2016
DOI: 10.1038/srep36487
|View full text |Cite
|
Sign up to set email alerts
|

EEG Spectral Dynamics of Video Commercials: Impact of the Narrative on the Branding Product Preference

Abstract: Neuromarketing has become popular and received a lot of attention. The quality of video commercials and the product information they convey to consumers is a hotly debated topic among advertising agencies and product advertisers. This study explored the impact of advertising narrative and the frequency of branding product exposures on the preference for the commercial and the branding product. We performed electroencephalography (EEG) experiments on 30 subjects while they watched video commercials. The behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 70 publications
2
26
0
3
Order By: Relevance
“…In the current research, the emotions and opinions of the user have been used as a hidden variable to bridge EEG signal and self-reported metrics to evaluate the impact of advertisement and its power to influence purchasing. In the literature, research has been done on the relationship of Theta wavelength with emotion and the relationship of Beta Wavelength with emotion (Lucchiari and Pravettoni, 2012 ; Wang et al, 2016 ). Considering that EEG signals contain components at many other frequencies, it is worth further investigation of the relationship between EEG signal and emotion, and how they impact a decision to make a purchase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current research, the emotions and opinions of the user have been used as a hidden variable to bridge EEG signal and self-reported metrics to evaluate the impact of advertisement and its power to influence purchasing. In the literature, research has been done on the relationship of Theta wavelength with emotion and the relationship of Beta Wavelength with emotion (Lucchiari and Pravettoni, 2012 ; Wang et al, 2016 ). Considering that EEG signals contain components at many other frequencies, it is worth further investigation of the relationship between EEG signal and emotion, and how they impact a decision to make a purchase.…”
Section: Discussionmentioning
confidence: 99%
“…Lucchiari and Pravettoni observed that EEG signals with a frequency of 16–31 Hz (i.e., Beta wave) could be modulated by the experience of pleasure when a consumer was presented with a favorite brand (Lucchiari and Pravettoni, 2012 ). In 2016, Wang, Chang and Chuang found that a narratives structure in video commercials induced higher EEG signals with a frequency band of 4–7 Hz (i.e., higher Theta) power of the left frontal region resulting in higher preference for branded products (Wang et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…One of the major limitations of EEG studies is the small sample size due to the complexity of the technology, and the cost and time‐consuming nature of EEG data collection. The sample size in our EEG study ( n = 65) is considerable large compared to most EEG studies in economic decision making (e.g., n = 40, Baldo, Parikh, Piu, & Müller, ; n = 18, Khushaba, Wise, Kodagoda, Louviere, Kahn, & Townsend, ; n = 12, Murugappan, Murugappan, & Gerard, ; n = 33, Ravaja et al, ; n = 30, Wang, R. W. Y., Chang, & Chuang, ; n = 30, Wei, Wu, Wang, Supratak, Wang, & Guo, ) and we used a within‐subject design to increase the number of observations. However, there have been sample size concerns that may affect the reliability of EEG studies in general (e.g., Bernheim, , Button, Ioannidis, Mokrysz, Nosek, Flint, Robinson, & Munafò, ).…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…Interregional theta synchronization was regarded as being related to the integration of functions in different brain regions ( Sauseng et al , 2010 ). The parietal region has involved in cognitive integration ( Wang et al , 2016 ).…”
Section: Discussionmentioning
confidence: 99%